Генетическая чистота семян – актуальный вопрос современной генетики и селекции растений - Акинина, Г.Е.; Тереняк, Ю.Н.; Шарыпина, Я.Ю.; Попов, В.Н. (Фактори експериментальної еволюції організмів, 2016)
Aim. The genetic purity of hybrids of sunflower seeds according to the standard ISO/TR 17622:2015 and correlation of the obtained data with plant uniformity in the field were studied. Methods. The genetic purity of sunflower hybrid samples using SSR-markers according to ISO/TR 17622:2015 was evaluated. Morphological traits during vegetation period in the field were registered. Statistical analysis of the obtained data was used. Results. Sixteen pairs of SSRprimers were allowed to analyze the genetic purity of 9 samples of sunflower hybrids. The laboratory data was highly positive correlated with plants uniformity in the field. Conclusions. Based on the obtained results it is necessary to approve ISO/TR17622:2015 in Ukraine and to develop threshold of genetic purity of sunflower seeds on the state level. Keywords: genetic purity of seeds, sunflower, SSR-markers, morphological traits, international standards.